STRATEGI BERTAHAN MASYARAKAT DENPASAR PADA MASA PANDEMI COVID- 19 (STUDI PADA PENERIMA PROGRAM STIMULUS PIP2) - I Ketut Sida Arsa; Ni Made Ary Widiastini; Fajar Yualida Isti Koma (Jurnal Kewirausahaan dan Bisnis, 2021)
The pandemic has an impact on the economic decline of the people in Bali, especially in Denpasar, which is the provincial capital. The government has taken various ways to help people survive in difficult times. This study aims to analyze and describe the resilience strategy of the Denpasar City community during the COVID-19 pandemic by observing the recipients of the PIP2 (Pandemic Incubation Program) stimulus program. Collecting research data using a questionnaire method (Google Form), interviews with respondents (either directly or indirectly/WhatsApp), and documentation. The data were analyzed descriptively qualitatively using a cultural studies approach. In this study, it was found that the stimulus program provided by the Denpasar City Government was welcomed by people who had a Denpasar ID card by submitting a proposal for submitting funds by showing the business being developed. Capital in the form of cash received can be used to expand their business even though only a few participants are able to survive until the program ends. In addition to continuing to innovate products through direct or by WhatsApp discussions with a business incubator as a companion, participants who received the PIP2 stimulus program also used social media to sell products.Keywords: Community, Denpasar, Program, Resilience, Stimulus, Strategy